French intellectuals and politics from the Dreyfus Affair to the Occupation - Drake, David, 1946- (French politics, society, and culture series., 2005)
This accessible and readable account analyses the political stances adopted by French writers and artists from the end of the nineteenth century to the Liberation. Opening with the 'Birth of the Intellectuals' during the Dreyfus Affair in the 1890s, it traces the political commitment of French intellectuals through World War One, and their subsequent responses to communism, pacifism, surrealism, the rise of fascism and the Occupation. It is a companion volume to Drake's Intellectuals and Politics in Post-War France (Palgrave Macmillan, 2002) and will be of interest to students of French cultural and intellectual history.